A Morphosyntactic Analysis on Narrative Writing of the Fresh Year Students’s of Management Informatics AMIK MEDICOM: Morphosyntactic Analysis - Masriani Mery Rosmida Silalahi; Siwi Rakasiwi (Journal of Classroom Action Research, 2022)
The purpose of the research is to analyze about morphology and sintactic structure in writing an English narrative essay. Morphology and Sintax are very important studies in learning English. Morphology is the study of how words are structured and how they are put together from smaller part, as morphemes are the smallest significant units of grammar. Meanwhile syntax discusses how sentences are structured. The purposes of this research are to cover the students morphosintactic errors operating on the students of the management informatics students’ narrative writing and how these errors affect the whole clause structure, the inflectional morphemes, derivational morphemes and the pattern of clause structure in the students narrative writing. The method used in this reserch is qualitative describtion where the data sources are taken from the fresh year students narrative writing. The finding revealse are two kinds of morphology, they are derivational and inflectional. Affixes such as suffixes, infixes, prefixes, ablaut and reduplication are kinds of derivational morphology, meanwhile plural, possessive, past time, progressive, comparative, and superlative are kinds of inflectional morphology. Syntactically, the errors occur becuse of not being aware how to build a phrase or a sentence in English. They write more than one verb in a phrase or a sentence which does not need but one. As well they are not sure about word order in English and how to build a simple sentence. They like to miss subject or object pronoun in their sentence. We can explain that by saying that all these forms do not exist in Bahasa Indonesia (Indonesian Language), resulting in the tendency for the students to omit or add these forms in their writing. Too many clauses in one sentence often occur in their sentece.